A multi-platform mobile application to prevent and cure obesity in Mexico. - Vazquez Ascencio, Diana Marisol (2016)
Currently, Mexico holds one of the top 10 places suffering from obesity in Latin America (Montes, 2016). Culture, tradition and media have taught people over the years what they should eat using lies, myths or unreliable sources. In a developing country such as Mexico, trusting the media is common and people forget to question the certainty of things. People get uneducated and that is how they follow a pattern that could lead to a variety of diseases difficult and expensive to treat. The problem addressed in this research is that must Mexicans do not know how nor what to eat. The research is trying to avoid people having to start medical treatment by suggesting to change an unhealthy meal for a similar healthy meal that provides the energy and the nutrients necessary. Preventing is the first step to achieving the purpose of this project; if Mexicans adopt a healthy food regimen many food-related diseases could be prevented. The solution developed is a multi-platform mobile application that integrates a chat using a Natural Language Understanding API. The chat is a bot with whom users can message about food related topics and the purpose of the bot is to provide users with a suggestion to replace meals by giving them ideas of new meals and healthy recipes. Recipes given to the user are based on a whole-foods plant-based diet; this diet suggest meals based on fruits, vegetables, tubers, whole grains, and legumes. Researchers from the Physicians Committee for Responsible Medicine (2013) state that plant-based diets may work better for weight loss, because they do not focus on portion control or calorie counting. The research executed an evaluation on Mexican volunteers who believe the solution was good and they may continue to use it if they could, they found the interface easy to use and understand, but the arrangement of the sections was confusing due to the order of actions. However, results on a change of their food regimen could not be recorded since in order to see changes on a user food-regimen the application must be user for a longer period of time. After the development was evaluated it was noticeable that more improvements have to be done in order to achieve the purpose of the application and become an efficacious technology-based weight-loss intervention.